Ionic effects on the transport characteristics of nanowire-based FETs in a liquid environment - Nozaki, Daijiro; Kunstmann, Jens; Zoergiebel, Felix; Pregl, Sebastian; Baraban, Larysa; Weber, Walter M.; Mikolajick, Thomas; Cuniberti, Gianaurelio (Giovanni) (Nano Research, 2014)
For the development of ultra-sensitive electrical bio/chemical sensors based on nanowire field effect transistors (FETs), the influence of the ions in the solution on the electron transport has to be understood. For this purpose we establish a simulation platform for nanowire FETs in the liquid environment by implementing the modified Poisson-Boltzmann model into Landauer transport theory. We investigate the changes of the electric potential and the transport characteristics due to the ions. The reduction of sensitivity of the sensors due to the screening effect from the electrolyte could be successfully reproduced. We also fabricated silicon nanowire Schottky-barrier FETs and our model could capture the observed reduction of the current with increasing ionic concentration. This shows that our simulation platform can be used to interpret ongoing experiments, to design nanowire FETs, and it also gives insight into controversial issues such as whether ions in the buffer solution affect the transport characteristics or not. [Figure not available: see fulltext.] © 2013 Tsinghua University Press and Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2023-03-20
Keywords: biosensors; Landauer model; nanowire field effect transistors (FETs); Poisson-Boltzmann theory; silicon nanowires